CML38 is involved in NO-induced inhibition of hypocotyl elongation in Arabidopsis - Wang, Dongsheng; Li, Zhaoyun; Zhang, Xiaoduo; Bian, Yanjie; Liu, Weizhong (Frontiers in Plant Science, 2025)
Calcium ions (Ca2+) are vital in plants, functioning both as structural cellular components and key secondary messengers that regulate growth, development, and stress responses. Nitric oxide (NO), a ubiquitous gaseous signaling molecule in organisms, also modulates diverse plant physiological processes. These two signaling molecules form a bidirectional interaction network, though the molecular mechanisms underlying their crosstalk remain poorly understood. Previous studies suggest that the calmodulin-like (CML) protein family mediates the interplay between NO and Ca2+ signaling. Our earlier RNA-seq data indicated that CML38 expression is responsive to exogenous NO in Arabidopsis seedlings, prompting the hypothesis that NO and Ca2+ signaling may interact with each other via CML38 regulation. To test this hypothesis, we employed Arabidopsis thaliana as a model plant and integrated genetic, biochemical, and molecular approaches to elucidate CML38’s role in NO-mediated hypocotyl growth inhibition. Our findings demonstrate that NO treatment significantly suppresses hypocotyl elongation in wild-type plants but not in CML38 loss-of-function mutant. CML38 binds Ca2+ and its calcium-binding capacity is unaffected by NO. Transcriptomic analysis revealed that CML38 participates in the crosstalk between NO and Ca2+ signaling, light signaling, as well as phytohormones. This study advances our understanding of the NO-Ca2+ interaction network in plants and provides insights into the molecular mechanisms by which these signals coordinately regulate plant growth and stress adaptation.